The Philosophy of Architecture and the Architects of Tomorrow: A Framework for the 2034 World Cup - Taha, Salma (Journal of Posthumanism, 2025)
Interest in the academic curriculum should not contradict with the preparation of students for the labor market, countries go through periods characterized by huge development leaps that can not be repeated for generations, so students must be involved in the follow-up of large projects to gain experiences from them, we sought in this paper to note the importance of good preparation for architecture and planning students by involving them in strategic and development work and large events organized by their countries, which are accompanied by huge construction works for infrastructure, services, public utilities, etc. The paper began by identifying the problem, which is the lack of interest in training architecture students to stand on the large works that are held in their countries, by following the approach of the philosophy of architecture, which allows them to launch towards broad scientific and practical horizons, and the goal is to obtain experiences that are difficult to obtain practically for long periods of time, and explain that this requires good knowledge of scientific requirements through regular study with scientific foundations such as planning, (and urban design) sustainable urban, the concept of sustainability, and auxiliary tools such as artificial intelligence and its role In the advancement of architecture, then clarifying the relationship between philosophy and architecture through.